Negociação de sentidos-e-significados sobre as aulas de inglês e o caderno de Língua Inglesa da Secretaria de Educação do Estado de São Paulo: uma pesquisa crítica de colaboração - Andrade, Fernanda Amaral de (2012)
This paper aims at 1) inferring and analyzing the senses-and-meanings of a public school English teacher, regarding her classes using the English language book provided by the São Paulo Secretary of State for Education (SEE-SP) and; (2) analyzing the interaction between the teacher-participant and teacher-researcher in order to understand how the negotiation of senses-and-meanings between them took place. In view of discussing the senses-and-meanings of the teacher and the concept of collaboration, this research is based on the Socio-Cultural-Historical perspective of development, learning, mediation and the zone of proximal development (ZPD) of Vygotsky (1930, 1934), and on the idea of language as a privileged psychological mediator element in the formation of critical and reflective teachers. Regarding language, it was necessary to discuss the critical-reflective notion based on Freire (1970/2004); Smyth (1992); Pérez Gómez (1992); Giroux (1992, 2000); McLaren (2000) and; the official documents such as Parâmetros Curriculares Nacionais (1998) and Orientações Curriculares (2006). This research relies on the concept of critical collaboration research Pccol - (MAGALHÃES, 2007, 2009, 2011), in which all research participants have active roles in building and transforming knowledge. The delimitation of the corpus was developed using the data collected in a public school of São Paulo, and was composed of 2 participants: the teacher-researcher and the teacher-participant. The analyzed and discussed data were generated from the observation and diário de campo of one Ensino Médio class; recording of one Ensino Fundamental class; and the recording of four reflective sessions between teacher- researcher and teacher-participant. The categories used for the data analysis were developed by the researcher and were based on the TSHC (VYGOTSKY,1930, 1934) and the concept of collaboration (MAGALHÃES, 2007, 2009, 2011). The results of the analysis indicate that the negotiation among participants created the possibility, through a collaborative review of their practices, of re-signification of their actions before the English language book provided by SEE-SP